Air pollution emissions from a steel mill plant using electric arc furnace - Taib, Mohamad Rozainee (1995)
This study measures particles and gaseous emissions from a new steel mill plant using electric arc furnace system. The content of cadmium, lead, zinc, iron, and copper were analyzed using Atomic Absorption Spectrometer (AAS) and the compositions of stack gas (NO, NO2 and SO2) were measured using a Greenline Combustion Gas Analyzer. Results obtained showed that electric arc furnace system eliminated the problem of SO2 and NOx emission from steel smelting process. Detailed discussion of this study is available in the attached full text article.